Density of Dermatophagoides spp. and Its Relationship with House-dust Mite Specific Serum IgE in Persistent Asthma - Annisa Mulia Anasis; Anna Rozaliyani; Heri Wibowo (Molecular and Cellular Biomedical Sciences, 2020)
Background: Asthma is a chronic inflammation of the bronchial tree that emerges as a response to exogenous factors, such as allergens, irritants, and infections. Some asthmatic patients had been reported having symptoms of asthma due to house-dust mites (HDM) allergen exposure. It is associated with immune responses which were increased in the form of specific Immunoglobulin E (IgE) production against HDM allergens. This case-control study aimed to determine the HDM profiles in persistent asthmatic patients, including density of mites, as well as its relationship with specific IgE anti-HDM serum levels.Materials and Methods: A total of 13 patients with persistent asthma and 12 control patients had their specific anti-HDM IgE levels examined using Immulite 2000 xpi. The house dust samples were taken and analyzed with the Fain method.Results: The results have shown that 69% of patients in the persistent asthma group and 25% of normal patients were positive for IgE anti-HDM. Dermatophagoides pteronyssinus is a predominant species with a total of 120 mites (83.9%) of 143 mites. Correlation analysis indicated a positive relationship between IgE anti-HDM levels within the serums of patients and the density of mites in the dust obtained from bedroom spaces (Spearmen Rho, R=0.35, p=0.04).Conclusion: Positive IgE anti-HDM patients in the persistent asthma group were higher (69%) than those in the clinically normal group (25%). The density of mites were dominated by D. Pteronyssinus. The bedroom-dust mites density revealed a positive correlation with serum IgE anti-HDM levels in persistent asthma patients.Keywords: asthma, density, Dermatophagoides spp.,IgE